The Concept of Nafs in Islamic Psychology and its Relevance to Student Development - Erwahyudin, Devid Dwi; Muzakki, Muhammad; Latief, Ardiansyah Mustofa (Al Misykat : Journal of Islamic Psychology, 2023)
The concept of nafs in Islamic psychology is important to guide students' development by combining spiritual and moral values in contemporary education. This study aims to analyze the concept of nafs in Islamic psychology and its relevance to student development. This research method is qualitative with a literature study approach. The result of this research is that the conscept of nafs in Islam is very important in education and self-development. A deeper understanding of this concept opens up opportunities to understand the role of nafs in the Qur'an and its application in Islamic guidance and counseling. This concept influences the formation of character, morale, and identity of students, and helps to overcome developmental challenges. Incorporating the values of the concept of nafs in learning also helps develop 21st century skills such as creativity, communication, and critical thinking. In character education, the concept of tazkiyatun nafs combines noble values, humanity, and religion, helping students become good in morals. The positive influence of the concept of nafs is also related to the understanding of the influence of the social and cultural environment on students' religious awareness and spirituality.